AN ANALYTICAL STUDY ON WOMEN EMPOWERMENT THROUGH SOCIAL MEDIA - V. SINJITHA *; R. JANSI RANI (The Journal of Research ANGRAU, 2022)
The study conducted during 2021–22 aimed to evaluate the socio-demographic profile of educated homemakers between the age group of 34 and 54 to recognize the influence of social media and to realize the impact of social media on women home makers. The adoptive structuration theory was used to enhance homemakers’ capacities by improving their technology acceptance among people who are unable to work independently and compelled to rely on their spouses for financial assistance. The results of the study showed that 90 percent of the homemakers were familiar with online commerce and social media utilization, which isn’t always feasible for earning additional money by homemakers because they’re overburdened with domestic responsibilities. However, the respondents could gain valuable insights into technology adoption.